Virulence and Genomic Feature of Multidrug Resistant Campylobacter jejuni Isolated from Broiler Chicken - Hao, Haihong; Ren, Ni; Han, Jing; Foley, Steven L.; Iqbal, Zahid; Cheng, Guyue; Kuang, Xiuhua; Liu, Jie; Liu, Zhenli; Dai, Menghong; Wang, Yulian; Yuan, Zonghui (Frontiers in Microbiology, 2016)
The aim of this study was to reveal the molecular mechanism involved in multidrug resistance and virulence of Campylobacter jejuni isolated from broiler chickens. The virulence of six multidrug resistant C. jejuni was determined by in vitro and in vivo methods. The de novo whole genome sequencing technology and molecular biology methods were used to analyze the genomic features associated with the multidrug resistance and virulence of a selected isolate (C. jejuni 1655). The comparative genomic analyses revealed a large number of single nucleotide polymorphisms, deletions, rearrangements, and inversions in C. jejuni 1655 compared to reference C. jejuni genomes. The co-emergence of Thr-86-Ile mutation in gyrA gene, A2075G mutation in 23S rRNA gene, tetO, aphA and aadE genes and pTet plasmid in C. jejuni 1655 contributed its multidrug resistance to fluoroquinolones, macrolides, tetracycline and aminoglycosides. The combination of multiple virulence genes may work together to confer the relative higher virulence in C. jejuni 1655. The co-existence of mobile gene elements (e.g. pTet) and CRISPR-Cas system in C. jejuni 1655 may play an important role in the gene transfer and immune defense. The present study provides basic information of phenotypic and genomic features of C. jejuni 1655, a strain recently isolated from a chicken displaying multidrug resistance and relatively high level of virulence.